Exploring the Mechanism for Promoting the High Quality Development of Ideological and Political Classroom Teaching - Liu, Yijing (Journal of Theory and Practice of Social Science, 2023)
Introducing high-quality development requirements into ideological and political classrooms in universities, in response to a series of drawbacks such as outdated teaching concepts, single teaching methods, and outdated feedback methods in traditional ideological and political classroom teaching, a development mechanism for two-way interaction between ideological and political classrooms and red clubs is explored to improve the effectiveness of ideological and political courses. Constructing ideological and political classroom teaching as the main body, with red club activities and exchanges as the two wings, to activate the acceptance ability and interest of educational objects in ideological and political courses, thereby promoting the high-quality development of ideological and political classroom teaching.